Constitutive Overexpression of the OsNAS Gene Family Reveals Single-Gene Strategies for Effective Iron- and Zinc-Biofortification of Rice Endosperm - Johnson, Alexander A. T.; Kyriacou, Bianca; Callahan, Damien L.; Carruthers, Lorraine; Stangoulis, James; Lombi, Enzo; Tester, Mark (PloS one, 2011)
Rice is the primary source of food for billions of people in developing countries, yet the commonly consumed polished grain contains insufficient levels of the key micronutrients iron (Fe), zinc (Zn) and Vitamin A to meet daily dietary requirements. Experts estimate that a rice-based diet should contain 14.5 µg g(-1) Fe in endosperm, the main constituent of polished grain, but breeding programs have failed to achieve even half of that value. Transgenic efforts to increase the Fe concentration of rice endosperm include expression of ferritin genes, nicotianamine synthase genes (NAS) or ferritin in conjunction with NAS genes, with results ranging from two-fold increases via single-gene approaches to six-fold increases via multi-gene approaches, yet no approach has reported 14.5 µg g(-1) Fe in endosperm. Three populations of rice were generated to constitutively overexpress OsNAS1, OsNAS2 or OsNAS3, respectively. Nicotianamine, Fe and Zn concentrations were significantly increased in unpolished grain of all three of the overexpression populations, relative to controls, with the highest concentrations in the OsNAS2 and OsNAS3 overexpression populations. Selected lines from each population had at least 10 µg g(-1) Fe in polished grain and two OsNAS2 overexpression lines had 14 and 19 µg g(-1) Fe in polished grain, representing up to four-fold increases in Fe concentration. Two-fold increases of Zn concentration were also observed in the OsNAS2 population. Synchrotron X-ray fluorescence spectroscopy demonstrated that OsNAS2 overexpression leads to significant enrichment of Fe and Zn in phosphorus-free regions of rice endosperm. The OsNAS genes, particularly OsNAS2, show enormous potential for Fe and Zn biofortification of rice endosperm. The results demonstrate that rice cultivars overexpressing single rice OsNAS genes could provide a sustainable and genetically simple solution to Fe and Zn deficiency disorders affecting billions of people throughout the world.